Microbial properties of soil fertilized by sewage sludge and cultivated with energy crops - Górska, Ewa Beata; Stępień, Wojciech; Olejniczak, Izabella; Pietkiewicz, Stefan; Halaji, Hazem M.; Kowalczyk, Paweł (Studia Ecologiae et Bioethicae, 2016)
The microbial activity of soil enriched with sewage sludge and cultivated with energy crops, is little known. The aim of this study was to assess the impact of sewage sludge fertilization on selected microorganisms in soil cultivated with the following crops: Miscanthus (Miscanthus x giganteus Greef et Deu), Virginia mallow (Sida hermaphrodita (L.) Rusby) and Common Osier willow (Salix viminalis L.). Sewage sludge was used in two rates 10 and 20 t/ha dry weight (DW). The numbers of total coliforms bacteria, sulphate-reducing spore-forming bacteria, Proteus sp., saprophytic, thermophilic and aerobic spore-forming bacteria were examined. Sewage sludge increased the number of coliforms and sulphate-reducing spore-forming bacteria, and stimulated the growth of saprophytic and thermophilic bacteria. Cultivation of Miscanthus limited the number of coliforms bacteria, while Virginia mallow and Miscanthus reduced the number of sulphate- -reducing spore-forming bacteria. Common Osier willow stimulated the growth of saprophytic bacteria in the soil, while Virginia mallow the number of spore-forming bacteria. Our results revealed that microbial activity of soil expressed as the number of selected bacterial groups, depends not only on the applied rate of sewage sludge fertilizer, but also on the cultivated energy crop.